AWARENESS OF CRYO ELECTRO TOMOGRAPHY AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
CryoElectronomography (CryoET) is indeed an imaging method used to create high resolution ( 1-4 nm) threedimensional viewpoints of specimen, usually physiological macro molecules as well as cell lines. CryoET is really a highly specialised implementation of scanning electron microscopy, cryomicroscopy, whereby the specimens are scanned since they are tilted, triggering a series of image data that can be processed to create a 3D image, analogous to 3D images, similar to a CT scan of the human body. This survey was done to assess the awareness of cryoelectrotomography among dental students. This was a questionnaire-oriented cross-sectional type of survey comprising 100 dental college students in Chennai. A self-designed questionnaire comprising ten questions based on the knowledge and awareness about cryo-electron tomography among dental college students. Questionnaires were circulated through an online website survey planet.The questions explored the awareness of using cryo-electron tomography as a tool to study various biological applications. After the responses were received from 100 participants, data was collected and analysed.7% are aware of cryo-electron tomography. 3% are aware of the mechanism of action of cryoelectron tomography. 5% are aware of the diagnostic applications of cryoelectron tomography. 3% are aware of the limitations of cryo-electron tomography. 91% are willing to learn about cryoelectron tomography. This study concluded that dental students showed less knowledge and awareness toward cryoelectrotomography. There are large gaps in the knowledge and attitudes requiring strong remedial measures.